Enhanced Quaternary Exhumation in the Central Three Rivers Region, Southeastern Tibet - Shen, Xiaoming; Tian, Yuntao; Wang, Ying; Wu, Lin; Jia, Yingying; Tang, Xiudang; Lei, Haijia; Yuan, Xiaoping; Ge, Yukui; Liu-Zeng, Jing (Frontiers in Earth Science, 2021)
The roles of tectonics and climate in the global increased erosion rates during the Quaternary have been the subject of active debate. The Three Rivers Region, strongly influenced by continental convergence between India and Eurasia and change in Asian monsoon climate, is an ideal place to study the interactions between tectonics and surface processes. Here we report new apatite (U-Th)/He data from an elevation transect that reveal a phase of rapid exhumation since ∼2.6 Ma in the Dulong batholith in the central Three Rivers Region, southeastern Tibetan Plateau. Based on stream profile analysis and compiled thermochronological data in the region, we demonstrate that the tectonic uplift caused by the high-strain at the corner of Indian-Eurasia convergence is responsible for the enhanced exhumation in the central Three Rivers Region in the Quaternary. Our new results highlight that the continuous plate convergence towards the plateau interior has dominated the uplift and deformation in the southeastern Tibet in the Quaternary.